2018
DOI: 10.1038/s41398-018-0168-9
|View full text |Cite
|
Sign up to set email alerts
|

Carbamoylated erythropoietin modulates cognitive outcomes of social defeat and differentially regulates gene expression in the dorsal and ventral hippocampus

Abstract: Cognitive deficits are widespread in psychiatric disorders and frequently as debilitating as the affective component. Widely prescribed antidepressants for treating depressive disorders have limited efficacy in normalizing cognitive function. Erythropoietin (Epo) has been shown to improve cognitive function in schizophrenia and treatment resistant depressed patients. However, the potent elevation of red blood cell counts by Epo can cause hematological complications in non-anemic patients. We investigated a che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 55 publications
0
25
0
1
Order By: Relevance
“…The apparent lack of hematopoietic cascade activation raises interesting questions regarding CEPO's mechanisms of action in mediating behavioral effects which are comparable to EPO (6,16). Gene expression studies have shown that EPO (16) and CEPO (11) share an overlap in the neurotrophic factors that they induce in the hippocampus, such as BDNF, VGF and neuritin. These three neurotrophic molecules have been previously shown to independently produce antidepressant-like and cognitive enhancing effects in rodent models (17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The apparent lack of hematopoietic cascade activation raises interesting questions regarding CEPO's mechanisms of action in mediating behavioral effects which are comparable to EPO (6,16). Gene expression studies have shown that EPO (16) and CEPO (11) share an overlap in the neurotrophic factors that they induce in the hippocampus, such as BDNF, VGF and neuritin. These three neurotrophic molecules have been previously shown to independently produce antidepressant-like and cognitive enhancing effects in rodent models (17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Erythropoietin was purchased from Prospec Bio (Israel) and carbamoylated in 1 mg aliquots as previously reported (5,11). Briefly, EPO was deprotonated in a high pH (pH = 8.9) borate buffer and then exposed to potassium cyanate for 16hr at 36 °C.…”
Section: Materials and Methods: Carbamoylation Of Epomentioning
confidence: 99%
See 1 more Smart Citation
“…CEPO was produced as per our CEPO characterization study. 13 RNA Isolation, cDNA Synthesis, and RT-qPCR RNA isolation was carried out using an Invitrogen RNAqueous Phenol-Free Total RNA Isolation Kit (AM-1912) following the manufacturer's instructions.…”
Section: Ngepo and Cepomentioning
confidence: 99%
“…11 The existence of the IRR is supported by the binding affinity measurements of EPO's carbamoylated form (CEPO), 12 in which we found that seven surface lysine residues were carbamoylated. 13 CEPO loses the ability to activate the classical EPOR/EPOR homodimer conformation and has no hematopoietic activity in-vivo or invitro. 12 However, CEPO retains EPO's neuroactive affects, implying that not only is EPOR/EPOR not mediating these effects but also that CEPO is a selective agonist of the IRR.…”
Section: Introductionmentioning
confidence: 99%